1997
DOI: 10.1021/ja963112s
|View full text |Cite
|
Sign up to set email alerts
|

Three-Electron SN2 Reactions of Arylcyclopropane Cation Radicals. 2. Steric and Electronic Effects of Substitution1

Abstract: The nucleophilic substitution reactions on substituted arylcyclopropane cation radicals were studied by a combination of methods including product studies, time-resolved laser flash photolysis, kinetic isotope effects, and quantum chemical calculations. The reactions were found to proceed stereospecifically with inversion of configuration, with high regioselectivity for nucleophilic attack at the more substituted carbon atom, and with very small steric effects. Electronic effects on the nucleophilic substituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
87
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 48 publications
10
87
0
Order By: Relevance
“…Dinnocenzo et al have observed that on ionization 1-phenyl-2-alkylcyclopropanes relax to structures where the PhC À C bond is lengthened to 1.7-1.8 , but is never fully cleaved (in the absence of nucleophiles, arylÀalkyl cyclopropanes do not epimerize upon oxidation). [14] Obviously the OTMS group has a more profound influence on the electronic structure of the cyclopropane radical cation than the phenyl group, as cyclopropyl silyl ethers undergo a multitude of radical cationic fragmentation, addition and rearrangement reactions. [16][17][18][19] Calculations on the model compound, 1-methoxy-1,2-dimethylcyclopropane 3, show that the strong distortions on ionization persist even if the OTMS group is replaced by an OMe group (but 3 a is 6.3 kcal mol À1 more stable than 3 b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dinnocenzo et al have observed that on ionization 1-phenyl-2-alkylcyclopropanes relax to structures where the PhC À C bond is lengthened to 1.7-1.8 , but is never fully cleaved (in the absence of nucleophiles, arylÀalkyl cyclopropanes do not epimerize upon oxidation). [14] Obviously the OTMS group has a more profound influence on the electronic structure of the cyclopropane radical cation than the phenyl group, as cyclopropyl silyl ethers undergo a multitude of radical cationic fragmentation, addition and rearrangement reactions. [16][17][18][19] Calculations on the model compound, 1-methoxy-1,2-dimethylcyclopropane 3, show that the strong distortions on ionization persist even if the OTMS group is replaced by an OMe group (but 3 a is 6.3 kcal mol À1 more stable than 3 b).…”
Section: Resultsmentioning
confidence: 99%
“…[1,2,10] The nucleophilic ring opening of cyclopropyl radical cations under PET conditions, which takes place under inversion of the carbon center which is attacked by the nucleophile (Scheme 1), has been studied mainly by the group of Dinnocenzo. [11][12][13][14] In contrast to these results, we found that cyclopropyl silyl ethers undergo spontaneous fragmentation, sometimes followed by re-cyclisation to form new products, in absence of nucleophiles, [17][18][19] that is, under conditions where alkyl-or aryl-substituted cylopropanes do not even epimerize. [10] In cyclic systems intermolecular addition reactions lead predominately to the endo-addition products, which is caused by the selectivity of initial fragmentation (Scheme 2).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…These conclusions are in full accord with the results of ab initio calculations (B3LYP/6-31G*), which documented the principal structural features and the charge density distribution in the radical cation, 1 •+ . 9 The divergent signal directions for the two pairs of secondary cyclopropane protons document an interesting stereoelectronic effect. To understand the nature of this effect, it is crucial to assign the orientation of these protons relative to the phenyl group.…”
mentioning
confidence: 99%
“…4i Finally, conjugation with a delocalized π-system also stabilizes structure type B, as indicated by calculations on vinylcyclopropane 8 and phenylcyclopropane radical cations. 9 The research described in this paper was undertaken to provide experimental evidence for the prevailing structure type of phenylcyclopropane radical cation (1 •+ ). This species has not been characterized by either ESR or CIDNP spectrum as of this date.…”
mentioning
confidence: 99%